Monita: Android System for Monitoring Emergency Response for Mothers and Babies - Sumarti Endah Purnamaningsih Maria Margaretha; Dhiya Urrahman; Chrisnawati Chrisnawati; Yohakim Marwanta; Fahmi Baiquni (Indonesian Journal of Global Health Research, 2025)
Maternal and neonatal mortality remain significant public health challenges in Indonesia, particularly in regions with limited access to health services. This study presents the MONITA (Monitoring Ibu dan Bayi Tanggap Darurat) application, an Android-based platform designed to enhance early detection of maternal and neonatal complications and strengthen emergency response coordination. MONITA integrates a rule-based screening module following WHO standards, real-time GPS tracking, automatic emergency notifications, and a spatial dashboard for monitoring critical cases. The development process involved system architecture design, UI/UX implementation, prototype testing, and integration of local health data. Preliminary deployment demonstrated that MONITA enables faster identification of high-risk cases, improves communication between field health workers and referral facilities, and supports timely decision-making in emergency situations. The application has the potential to contribute to reducing maternal and neonatal mortality rates and optimizing emergency care in remote or resource-limited areas.